A Study of Postural Safety and Low-Cost Electromyography (EMG) Device Towards Grocery Workers in Kota Samarahan, Sarawak - Mohd Azrin, Mohd Said; Brian Egan, Jackson Tubam; Nor Kamaliana, Khamis; Aishah, Arsad (RMP Publication, 2020)
Body posture is one of the most important parts whenlifting an object as it can causesinjury if the wrong technique and body posture wereused. A worker will injure their low back if a badposture isnot in consideration. A good body posture isrecommended among workers to reduce the chance of injury while lifting and improve their postural safety. The main objectivesof this studyare to observe the body posture of the worker during lifting and study the comparison of using lower back support when lifting. It also investigates the muscle activity of the worker during heavy lifting using EMG and simulates the worker's movement using CATIA Software forRapid Upper Limb Assessment (RULA) results. The selected grocery waschosenin Kota Samarahan, Sarawak with 7 male respondents are identified to undergo this study. The results showthat the worker with lower back support tends to show raw EMG signal with lower muscle activity compared to without using lower back support. Thus, using belt support can reduce muscle activity by up to 67.4% compare to not wearing back support. Raw EMG signals also show 3010amplitude (mV) muscle activity if postural safety of the workers improved by following the NIOSH lifting Recommendations